Transmission Line Fault Distance Measurement based on Time Difference between Travelling Wave Reflection and Refraction - Šiožinys, V. (Elektronika ir Elektrotechnika, 2010)
The relay protection principles based on travelling wave are observed. Transmission line fault distance measurement algorithm based on time difference between travelling wave reflection and refraction is proposed. An algorithm, its mathematical prove, modelling results and errors are presented in article. The simple scheme calculation example is presented to describe fault location algorithm behaviour. Transmission line model with 4 lines which length is from 200 to 400 meters is used to represent algorithm. The distance to fault location calculated error is in range of 1–3%. Ill. 3, bibl. 4 (in English; summaries in English, Russian and Lithuanian).